Re defining and refining information literacy and reference services in the digital age : 15-16 August 2013, National Library Building, Singapore - Satellite-Meeting... (IFLA World Library and Information Congress Information Literacy Section and Reference & Information Services Section, 2013)
st,1/ws.c.1